The Role of IL-37 and IL-38 in Obstetrics Abnormalities - Wang, Mei (Frontiers in Medicine, 2021)
There are two fairly common complications during pregnancy, i.e. gestational diabetes mellitus (GDM) and pre-eclampsia, which are independent, but are also closely linked in prevalence in pregnant women, with potential serious adverse consequences. IL-37 and IL-38, which belong to the IL-1 superfamily, participate in anti-inflammatory responses. Dysregulation of IL-37 and IL-38 has been observed in many auto-immune diseases. IL-37 is substantially reduced in the umbilical cords and placentas of GDM subjects, but IL-37 is significantly induced in the placentas of pre-eclampsia patients, suggesting there are differential regulatory roles of IL-37 in obstetrics, despite IL-37 being an anti-inflammatory mediator. Furthermore, IL-38 is substantially increased in the umbilical cords and placentas of GDM subjects, but minimal difference is observed in the placentas from pre-eclampsia patients. These data imply that IL 38 is also regulated independently within the diseased placentas. This review provides some insight for both basic scientists and medical practitioners to manage these patients effectively.